Conformational transitions of poly(dA-bromo5dU) and poly(dA-iodo5dU) in solution. - Vorlícková, M (1992)
Extensive circular dichroism studies have been conducted with the title polynucleotides under various solution conditions. The studies provided the following information: (i) The halogen atoms in place of thymine methyl hinder the isomerization into X-DNA. (ii) The brominated but not iodinated polynucleotide isomerizes into Z-DNA in concentrated NaCl+NiCl2. The transition takes place at lower NiCl2 concentrations than with poly(dA-dT). (iii) The iodinated polynucleotide forms an unusual conformation in aqueous solution in which it is very stable. It isomerizes from this conformer into the usual B-type double helix in concentrated ethanol solutions. The isomerization is a two-state cooperative process. (iv) Both title polynucleotides undergo still another two-state cooperative transition in trifluorethanol solutions presumably into A-DNA showing a rather unusual circular dichroism spectrum.